Causes for Non-Adoption of Post Tsunami Rice Cultivation Practices (Indian Journal of Extension Education, 2011)
On December 26, 2004 for the first time in half of a century, India experienced the devastating effects of Tsunami, caused by a series of earthquakes. The Tsunami waves caused extensive damage to three states (Andhra Pradesh, Tamil Nadu and Kerala) and two Union Territories (Puducherry and Andaman and Nicobar Islands) in India.